Divergence in Cuticular Chemical Signatures between Isolated Populations of an Intraspecific Social Parasite - Lorenzi, M. Cristina; Azzani, Laura; Bagnères, Anne-Geneviève (Frontiers in Ecology and Evolution, 2017)
Parental care is costly enough that species exist which exploit the parental care of other individuals to rear their own brood, as social parasites do among social insects. Intraspecific, facultative social parasites use the nest and worker force of another colony of the same species to rear their own young as a reproductive strategy alternative to independent nest foundation. Intraspecific parasites face barriers similar to those of interspecific social parasites: they must bypass host nestmate recognition abilities and keep host workers under control. In the present study, we investigate the cuticular chemical signature of Polistes biglumis paper wasps when they behave as intraspecific social parasites and invade conspecific colonies. We performed our analysis on three geographically separated populations, which differ in their social structure; in one population foundresses regularly produce workers, whereas in the others they rarely do. We tested whether the chemical signature of females which parasitize conspecific colonies resembles that of females who found their colonies, and if this effect is similar among populations with/without workers. Our results show that in the two populations where foundresses produce virtually no workers, the hydrocarbon signatures of intraspecific social parasites were not chemically distinct from those of the foundresses. In contrast, in the population where foundresses usually produce workers, the hydrocarbon signatures of intraspecific social parasites had significantly larger proportion of long-chained and branched hydrocarbons than those of foundresses. These characteristics may have evolved in that population to facilitate parasite exploitation of the host workforce, as long-chained and branched hydrocarbons are relevant as recognition and fertility cues. The lack of workers in the other populations may have relaxed the selection pressure that host workers impose on the chemical signature of intraspecific social parasites.